The body self and the frequency, intensity and acceptance of menopausal symptoms - Sakson-Obada, Olga; Wycisk, Jowita (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction: There are many studies on the concept of body image (usually understood narrowly as body acceptance) in menopausal women, but relationships between the body self and menopausal symptoms have not been explored yet. In the research discussed in this paper, a complex model of the body self, including its functions, body identity and body image, has been presented. Aim of the study was to explore the relationships between different aspects of the body self, and the frequency, intensity and acceptance of menopausal symptoms. Material and methods: The investigated sample consisted of 81 women (age: 51.8 ± 4.2 years; range: 45-58 years). The authors used an extended version of the Menopause Symptom List and the Body Self Questionnaire. Results: Perception of sensations, interpretation and regulation of emotions and physical states as well as body identity were the most important correlates of the intensity and frequency of menopausal symptoms (psychological, vasomotor and somatic). Among the body image aspects investigated in the study, the appearance evaluation was associated with the frequency of vasomotor and psychological symptoms. The level of acceptance of symptoms was only related to the ability to cope with emotions and physical needs. Conclusions: The findings indicate that aspects of the body self (which are stable personality traits) are significant for the way women experience menopausal symptoms.